Islamic jurisprudence perspectives on the practice of asset-based and asset-backed sukuk in Malaysia - Zakaria, Mohamad Zaharuddin; Abdul Aziz, Akhtarzaite (IIUM Press, 2017)
This research aims to analyze the Sharicah issues in asset-based and asset-backed sukuk in Malaysian practice and finally proposing some possible solutions to these issues. Most of the issues have remained controversial among sukuk players especially with regard to asset-based sukuk which is claimed as noncompliant with the Sharicah rules. These unsolved issues have posed huge constraints to investors especially from the Middle Eastern countries which perceive Malaysian sukuk as similar to conventional bond. Thus, the principles, terms and conditions of some sukuk issued in Malaysia have been revised in order to conform to the Sharicah rules. The method used in this study was mainly textual analysis to highlight the main characteristics of asset-based and asset-backed sukuk as practiced in Malaysia. Some selected term sheets of sukuk issued were analyzed to identify Sharicah issues. In addition, some Malaysian scholars were interviewed in order to get their views on these issues. It is found that these issues abound due to the conflicting opinions that stem from the different perceptions and interpretations of scholars on the textual evidence Mohamad Zaharuddin Bin Zakaria Akhtarzaite Abdul Aziz